2016
DOI: 10.1016/j.jmst.2016.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Superelasticity and Tunable Thermal Expansion across a Wide Temperature Range

Abstract: Materials that undergo a reversible change of crystal structure through martensitic transformation (MT) possess unusual functionalities including shape memory, superelasticity and low/negative thermal expansion. These properties have many advanced applications, such as actuators, sensors and energy conversion, but are limited typically in a narrow temperature range of tens of Kelvin.Here we report that, by creating a nano-scale concentration modulation via phase separation, the MT can be rendered continuous by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…27 Besides, the hypothesis that pretransition embryo growth explains or at least contributes to the invar effect is supported by experiments showing that a severe cold-work treatment can significantly change the thermal expansion behaviors. 19,[28][29][30][31] A second interesting effect of increasing the equilibrium ω upon cooling is a softening of the effective modulus. This softening counteracts the usual stiffening (increase of C 0 ) on cooling.…”
Section: Resultsmentioning
confidence: 99%
“…27 Besides, the hypothesis that pretransition embryo growth explains or at least contributes to the invar effect is supported by experiments showing that a severe cold-work treatment can significantly change the thermal expansion behaviors. 19,[28][29][30][31] A second interesting effect of increasing the equilibrium ω upon cooling is a softening of the effective modulus. This softening counteracts the usual stiffening (increase of C 0 ) on cooling.…”
Section: Resultsmentioning
confidence: 99%
“…It should be pointed out that there are no twins in WCZ (if twins existed in WCZ, there would be high fractions near the misorientation angles of 65°and 85°in misorientation distribution) even in TMAZ near WCZ, which is different from the ECAP [27][28][29][30][31], cold rolling [36] and hot compression [37]. This is due to the high temperature at the interface and the heavy plastic deformation during LFW (see Table 2).…”
Section: Microstructure Evolutionmentioning
confidence: 98%
“…In this work, commercially pure titanium (CP-Ti) instead of α + β titanium alloy was chosen to examine the recovery and recrystallization behaviors, together with the texture development, in view of the complex effect of prior β on the final texture distribution in α + β titanium alloys [26,27]. It is accepted that dynamic recrystallization is hard to occur for pure titanium due to its greater stacking fault energy (0.31 J/m 2 [28]).…”
Section: Introductionmentioning
confidence: 99%
“…It was forged at 1123 K into a bar with 55 mm in diameter and then rolled at 1073 K into a bar with 12 mm in diameter. The asrolled alloy has a single β phase microstructure with an average grain size of~5 μm and sub-grain size of~0.6 μm as well as a nanoscale Nb modulation with the domain size of 2-3 nm [20,24]. Three kinds of V-type circumferential notch specimens ( Fig.…”
Section: Materials Preparationmentioning
confidence: 99%
“…Our recent investigations showed that Ti2448 contains a nanoscale spatial modulation of Nb, which is created by the isostructural phase decomposition, and an in-situ elastically confined martensitic transformation was proposed to explain its novel nonlinear elasticity [19]. This leads to some unprecedented properties such as strong in strength, soft in modulus, ductile in toughness in combination with super-elasticity and entirely tunable thermal expansion from positive, via zero, to negative in a wide temperature range [20,21]. The nanoscale Nb modulation can stabilize the β phase and cause a successive atomic rearrangement via the up-hill Nb diffusion [22,23].…”
Section: Introductionmentioning
confidence: 99%